ISLAMIC PERSPECTIVES ON THE EXISTENCE OF SOUL AND ITS INFLUENCE IN HUMAN LEARNING (A Philosophical Analysis of the Classical and Modern Learning Theories) - Tabrani ZA; Masbur Masbur (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2015)
Islam believes in the existence of soul and its influence in human learning. Islam believes that human being consists of both body and soul, Islamic perspective on how a person learns from insani experience also differs compared to contemporary Western psychological perspective. This paper aims to provide a view Islam on the psychology of learning in terms of the two sides of the Ilahiyyah (Islam) and Insaniyyah (Psychology). This discussion will provide an overview of the concept of learning that Islam is divided into two sources: directly from Allah (Ilahiyyah) and through human experience (insaniyyah). Source God can be in the form of revelation, inspiration (inspiration), and a true dream (ru'ya sadiqah). Human experience can be in the form of conditioning, observation, and cognition. Moreover, this discussion would like to see contemporary learning theory from the Islamic perspectives. The Islamic perspectives will include Qur’anic verses, Prophetic Hadiths, stories of the Prophets and Companions, and the work of early Muslim scholars such as Ibn Sina and al-Ghazali using terms familiar to contemporary psychology.